Supportive supervision as an effective intervention in improving water, sanitation and hygiene facilities in government health facilities of Tamil Nadu - Subramaniam, Sudharshini; Selvavinayagam, T. S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Water, sanitation and hygiene (WASH) is one of the important components of Sustainable Development Goals which is essential for achieving any global health-related goals. WASH in health care facilities is prioritized as a necessary input to achieve health goals. Supportive Supervision has been established as an effective intervention in improving the performance of health care workers. This paper evaluates the role of supportive supervision in improving WASH facilities in the health care facilities of high priority districts of Tamil Nadu. Methods: The effectiveness of supportive supervision in improving WASH facilities was assessed through a pre-post experimental research design. World Health Organization proposed steps were followed while planning for the supportive supervision. Supervisory visits were made using checklists in all secondary level public health facilities in 7 High Priority Districts which were chosen based on the preliminary WASH survey conducted by UNICEF. The same health facilities were revisited after 3 months and supervised using the same checklist. Results: In the first supervisory visit, 41.6% of the health facilities (57 out of 137 facilities) were non- functional in terms of WASH score, while only 5.8% (8 out of 137 facilities) were fully functional. In the second visit, proportion of non- functional facilities had dropped from 41.6% to 7.3% and there has been an increase in the partially functional (52.6% to 71.5%) and fully functional facilities (5.8% to 21.2%) which was found to be statistically significant. Conclusions: Supportive supervision was able to show a significant improvement in the WASH facilities in all types of facilities.